Association of pretreatment neutrophil‐to‐lymphocyte ratio (NLR) and overall survival (OS) in patients with metastatic castration‐resistant prostate cancer (mCRPC) treated with first‐line docetaxel. (14th February 2014) - Nuhn, Philipp; Vaghasia, Ajay M.; Goyal, Jatinder; Zhou, Xian C.; Carducci, Michael A.; Eisenberger, Mario A.; Antonarakis, Emmanuel S.
<x xml:space="preserve">Abstract</x> Objective To determine whether the pretreatment neutrophil‐to‐lymphocyte ratio (NLR), a measure of systemic inflammatory response, is associated with overall survival (OS) in men receiving chemotherapy with docetaxel for metastatic castration‐resistant prostate cancer (mCRPC). Patients and Methods Records from 238 consecutive patients who were treated with first‐line docetaxel‐containing chemotherapy for mCRPC at a single high‐volume centre from 1998 to 2010 (and who had adequate information to enable calculation of NLR) were reviewed. Univariable and multivariable Cox regression models were used to predict OS after chemotherapy initiation. Results In univariable analyses, the NLR as a discrete variable (optimal threshold 3.0) was significantly associated with OS (P = 0.001). In multivariable analyses, a lower NLR (≤3.0) was associated with lower risk of all‐cause mortality (P = 0.002). In Kaplan–Meier analysis, the median OS was higher (18.3 vs 14.4 months) in patients that did not have an elevated NLR than in those with an elevated NLR (log‐rank; P < 0.001). Conclusions Men who were treated with first‐line docetaxel for mCRPC who had a low pretreatment NLR (≤3.0) had significantly longer OS. NLR may be a potentially useful clinical marker of systemic inflammatory response in predicting OS in men with mCRPC who receive docetaxel and may be helpful to stratify patients for clinical trials. These findings derived from a retrospective analysis need to be validated in larger populations in prospective studies, and in the context of different therapies.